Acknowledgement of sponsors for program bulan kemuncak inovasi dan kualiti UiTM 2025 - Zulkifli, Nur Wahida; Kamaruzaman, Hamim Aiman; Lay Kek, Teh; Abdul Hamid, Hisyam; Husain, Noreen (Faculty of Pharmacy, 2026)
The success of the Program Bulan Kemuncak Inovasi dan Kualiti held at Dewan Agung Tuanku Canselor (DATC), UiTM Shah Alam on 22 December 2025 would not have been possible without the generous support and commitment of our valued sponsors. Their contributions played a significant role in enhancing the overall experience of the programme and in recognising the participation and achievements of attendees through exciting lucky draw sessions.